SGLT2 Inhibitors: A Broad Impact Therapeutic Option for the Nephrologist - Granata, Antonio; Pesce, Francesco; Iacoviello, Massimo; Anzaldi, Massimiliano; Amico, Francesco; Catalano, Maria; Leonardi, Giuseppe; Gatta, Carmela; Costanza, Giusy; Corrao, Salvatore; Gesualdo, Loreto (Frontiers in Nephrology, 2022)
Since their introduction as antidiabetic drugs, SGLT2 inhibitors (SGLT2i) have come a long way, proving to be beneficial on cardiovascular and renal outcomes independently of diabetes status. The benefits go far beyond glycemic control, and both the cardio- and nephroprotection are underpinned by diverse mechanisms. From the activation of tubule glomerular feedback and the consequent reduction in hyperfiltration to the improvement of hypoxia and oxidative stress in the renal cortex, SGLT2i have also been shown to inhibit hepcidin and limit podocyte damage. Likewise, they improve cardiac metabolism and bioenergetics, and reduce necrosis and cardiac fibrosis and the production of adipokines, cytokines, and epicardial adipose tissue mass. In terms of outcomes, the efficacy has been demonstrated on blood pressure control, BMI, albuminuria, stroke, heart disease, and mortality rate due to cardiovascular events. Patients with chronic kidney disease and proteinuria, with or without diabetes, treated with some SGLT2i have a reduced risk of progression. The analysis of subgroups of individuals with specific diseases such as IgA nephropathy has confirmed this solid effect on renal outcomes. Given these overarching activities on such a broad pathophysiological background and the favorable safety profile that goes with the use of SGLT2i, it is now certain that they are changing our approach to clinical interventions for important outcomes with an impressive impact.